Party system types and party system institutionalization: comparing new democracies in East and Southeast Asia - Croissant, Aurel; Lorenz, Philip (Party politics, 2012)
This article is an overview of the types and level of institutionalization of party systems in seven young democracies in East and Southeast Asia. By applying Alan Siaroff’s typology of party systems, the analysis demonstrates that the party systems in Asia do not converge on a single format. The party systems under consideration also differ in the level of institutionalization. Party systems in Thailand, the Philippines and especially South Korea are stuck in an inchoate state. Even though there is considerable variation among the cases, the party systems in Indonesia, Mongolia and Taiwan can be considered as well institutionalized relative to the rest of Asia and moderately institutionalized when compared to Latin America. Furthermore, weak institutionalization correlates with volatile structures of party competition and cooperation in Thailand, whereas in South Korea and the Philippines party systems seem to be paradoxically stabilizing in a situation of protracted under-institutionalization, as both cases combine more or less stable party system patterns with weak institutionalization.